Improved Mode I fracture resistance of CFRP composites by reinforcing epoxy matrix with recycled short milled carbon fibre. (15th May 2016) - Cholake, Sagar T.; Moran, Grainne; Joe, Bill; Bai, Yu; Singh Raman, R.K.; Zhao, X.L.; Rizkalla, Sami; Bandyopadhyay, Sri
Highlights: Recycled short milled carbon fibres are proved advantageous to increase G IC of epoxy resin. Higher energy absorption through individual debonding and pull-out mechanisms is observed. Correlation between fracture toughness of matrix and composite is discussed. Abstract: This paper proves that incorporation of recycled short milled carbon fibre (SMCF) in epoxy resin can lead to the generation of significantly tougher carbon fibre reinforced polymer (CFRP) systems in a cost effective manner for infrastructural applications. Structural epoxy resin is modified by adding 5 and 10 wt.% of SMCF particles and the 'fracture toughness' of the modified matrix ( G IC M ) is observed to be increased by 300% and 700% respectively. Subsequently, the SMCF modified epoxy resins were used to fabricate unidirectional carbon fibre reinforced laminates and tested under Mode I crack opening. The SMCF reinforcement showed 50% and 64% improvement in the laminates fracture toughness ( G IC C ) after adding 5% and 10% SMCF by wt., respectively. Scanning electron microscope images of the fracture surface highlight improved debonding and pull-out mechanisms contributing to the additional fracture toughness, and at the same time there was no evidence of fibre clustering.